Association between acute heart failure and major cardiovascular events in atrial fibrillation patients presenting at the emergency department: an EMERG-AF ancillary study. (June 2021) - Coll-Vinent, Blanca; Varona, Mercedes; Martin, Alfonso; Carbajosa, José; Sánchez, Juan; Tamargo, Juan; Cancio, Manuel; Sánchez, Susana; del Arco, Carmen; Miró, Òscar; Ríos, José; García, Ana; et al.
Abstract : Background: There is little evidence concerning the impact of acute heart failure (AHF) on the prognosis of atrial fibrillation patients attending the emergency department (ED). Objective: To know the influence of AHF on adverse long-term outcomes in patients presenting with atrial fibrillation in ED. Design, setting and participants: Secondary analysis of a prospective, multicenter, observational cohort of consecutive atrial fibrillation patients, performed in 62 Spanish EDs. Exposure: Patients presenting with atrial fibrillation in ED were divided by the presence or absence of AHF at arrival. Outcome measures and analysis: Primary outcome: combination of 1-year all-cause mortality, major bleeding, stroke and other major cardiovascular events (MACE). Secondary outcomes: each of these events analyzed separately. Cox and logistic regression were used to investigate adjusted significant associations between AHF and outcomes. Main results: Totally, 1107 consecutive ED patients with atrial fibrillation attending ED were analyzed, 262 (23.7%) with AHF. The primary outcome occurred in 433 patients (39.1%), 1-year all-cause mortality in 151 patients (13.6%), major bleeding in 47 patients (4.2 %), stroke in 31 patients (2.8 %) and other MACE in 333 patients (30.1%). AHF was independently related to the primary outcome [odds ratio (OR), 1.422; 95% confidence interval (CI), 1.020–1.981; P = 0.037)] and 1-year MACE (OR, 1.797; 95% CI, 1.285–2.512; P = 0.001), but not to 1-year all-cause mortality, stroke or bleeding. Conclusions: The coexistence of AHF in patients presenting with atrial fibrillation in ED is associated to a worse 1-year outcome mainly due to MACE, but does not impact in overall mortality.